1992
DOI: 10.1111/j.1600-0587.1992.tb00015.x
|View full text |Cite
|
Sign up to set email alerts
|

Element concentrations in mosses and surface waters of western Canadian mires relative to precipitation chemistry and hydrology

Abstract: Concentrations of N, P, S, Na, K, Mg, Ca, Mn, Fe, Cu, Cd, Zn, Pb, Al, and AIA (acid insoluble ash) m mosses (three Sphagnum species and Tomenthypnum nitens, all hummock species) from a variety of mires, both ombrotrophic and minerotrophic, in the coastal western and central parts of Canada are considered in relation to surface water pH and concentrations of Na+, K+, Mg2+, Ca2+, Cl−, and SO42‐ Distinct west‐east concentration gradients were present for most elements in both mosses and water, but there were corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 44 publications
6
35
0
Order By: Relevance
“…Indeed, they could be expected to respond in a similar way than testate amoebae to humidity and nutrients gradients. Some variables not taken in account like niche competition, sensitivity to microclimatic variations, interstitial water conductivity or nutrients may be more important for bryophytes than for testate amoebae and could explain the relative weakness of the relationships observed here (Bragazza, 1997;Buttler et al, 1998;Malmer et al, 1992;Mitchell et al, 2000). However our results agree with a recent comparative ecological study of testate amoebae, bryophytes and vascular plants in fens and bogs, which showed that testate amoeba communities were more strongly correlated to all measured variables (conductivity, pH, magnesium, calcium and DWT) than bryophytes or vascular plants or both combined .…”
Section: Community-environment Relationships-micro-habitats and Dwtmentioning
confidence: 96%
“…Indeed, they could be expected to respond in a similar way than testate amoebae to humidity and nutrients gradients. Some variables not taken in account like niche competition, sensitivity to microclimatic variations, interstitial water conductivity or nutrients may be more important for bryophytes than for testate amoebae and could explain the relative weakness of the relationships observed here (Bragazza, 1997;Buttler et al, 1998;Malmer et al, 1992;Mitchell et al, 2000). However our results agree with a recent comparative ecological study of testate amoebae, bryophytes and vascular plants in fens and bogs, which showed that testate amoeba communities were more strongly correlated to all measured variables (conductivity, pH, magnesium, calcium and DWT) than bryophytes or vascular plants or both combined .…”
Section: Community-environment Relationships-micro-habitats and Dwtmentioning
confidence: 96%
“…The low nutrient Table 2 for explanation of sample codes. Right panel shows the correlation between the PC axes and the carbohydrate monomers (black arrows) and those supplementary variables (grey arrows) with a correlation coefficient ≤ −0.4 or ≥ +0.4 with PC1 and/or PC2 concentrations in hollow species from the peatland centre potentially reflects the lower nutrient retention capacity of hollows (Bragazza et al 2004), the prevailing direction of water flow and dissolved nutrients from hollows to lawns and hummocks in more continental climates (Eppinga et al 2010) or, alternatively, extra nutrient relocation from deeper depths by co-occurring vascular plant species in lawns and hummocks (Malmer et al 1992;Malmer et al 2003). As nutrient concentrations in Sphagnum plant material co-determine its degradability and speed of mineralisation (Damman 1988;Limpens and Berendse 2003;Straková et al 2012), differences in nutrient concentrations in Sphagnum may have direct implications for mineralisation rates and nutrient cycling in peatlands.…”
Section: Elementsmentioning
confidence: 99%
“…Based on ecohydrology and the consequent nutrient status, boreal peatlands are classified into two main trophic classes: minerotrophic and ombrotrophic (Rydin and Jeglum 2006). Minerotrophic peatlands, i.e., fens, receive nutrients from input water that drains nearby mineral soils (Ingram 1992) and they are richer in cations such as Mg 2+ , K + , and Ca 2+ (Malmer et al 1992). Minerotrophic fens can be further divided into three classes according to their nutrient availability: oligotrophic (poor), mesotrophic (intermediate) and eutrophic (rich) (Rydin and Jeglum 2006).…”
Section: Peatland Ecosystemsmentioning
confidence: 99%